New English Words for Describing the International English as a Current World Language Reality - Ivanova, Natalia K.; Merkulova, Nadezhda E. (Research in Language, 2021)
The evolution of the English language, its changing in the situation of language contacts and functioning of English as an international means of communication have created a need for a more systematic analysis of related phenomena. In this paper, new English words which apparently appeared due to globalization and internationalization, have been considered. On the basis of authoritative theoretical approaches and several e-dictionaries, the words selected by means of continuous sampling method (more than 200 units) were analysed in terms of their semantics, morphology and spelling. Then they were classified into several thematic groups: 1) new words for naming natural and artificial versions of current English; 2) words classified with regard to social accents and dialects; 3) neologisms that reflect the English language domain and its interaction with indigenous languages. The morphological analysis revealed the application of different processes of word-formation, including neologisms and forms created according to traditional English patterns. Sometimes play on words and homo-acronyms were used in order to reinforce the meaning and connotation. Compounding and blending were found to be the most productive means of words formation within the corpus, and stylistic neologisms, used to mark a certain underlying sense proved to be the second most frequent process. It is demonstrated that studying of the currently active processes of word formation in the English language used as an international communication tool emphasizes the interdisciplinary aspect of such research programs.